Analysis of PhET Virtual Laboratory in Nuclear Physics Course at Physics Education - Silvia Lutfiani; Iis Hisna Husna Takiah; Sean Resha Herdhiyatma; Ifa Rifatul Mahmudah (Universitas Islam Negeri (UIN) Mataram, 2023)
In the introductory physics course, conducting experiments and learning topics that seem abstract using a PhET virtual laboratory is necessary. With several previous research results showing that PhET has benefits in learning activities, this study aims to find out Physics Education students related to the usefulness of the PhET virtual laboratory in the introductory alpha decay Nuclear physics course. This research is a quantitative descriptive technique with the research variable of the Colorado PhET virtual laboratory in the Introduction to Nuclear Physics course on alpha decay material. The data collection technique is through a questionnaire method using a Likert scale of five answer choices marked by giving a negative to positive score. The population of the survey is all students of physical education, which is 79 people. However, only 71 people filled out the questionnaire. Characteristics of students who are 21 years old on average with computer/laptop skills on average 81%, interest in introductory physics courses as much as 77%, interest in practicum as much as 86%, and interest in learning topics as much as 61% it can be said that the laboratory virtual PhET is helpful in the learning process of the introductory alpha decay Nuclear physics course with a proportion of 86% of PhET virtual laboratories can help the learning process, 81% of PhET virtual laboratories are the preferred learning method, 80% of PhET virtual laboratories are engaging learning, 81% virtual laboratories PhET can be done independently, and 79.99% use of the virtual laboratory application is easy to use.